2013
DOI: 10.1021/cb300673e
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Urinary Metabolites for Diagnosing Multiple Sclerosis

Abstract: A definitive diagnostic test for multiple sclerosis (MS) does not exist; instead physicians use a combination of medical history, magnetic resonance imaging, and cerebrospinal fluid analysis (CSF). Significant effort has been employed to identify biomarkers from CSF to facilitate MS diagnosis; however none of the proposed biomarkers have been successful to date. Urine is a proven source of metabolite biomarkers and has the potential to be a rapid, non-invasive, inexpensive, and efficient diagnostic tool for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…A similar strategy involving oral formulation of high dose biotin, which serves as a cofactor for essential carboxylase enzymes required for fatty acid synthesis, has recently been demonstrated to provide benefit in patients with not-active progressive multiple sclerosis 39 . Intriguingly, taurine has previously been identified as a dysregulated metabolite in animal models of multiple sclerosis disease, including nonhuman primate models 40 , and its plasma levels can be used to distinguish PLP-induced experimental autoimmune encephalomyelitis (EAE) mice from naive controls 4144 . At a minimum, these findings demonstrate the utility of global metabolomic analyses in the identification of endogenous metabolites that can serve to modulate cellular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy involving oral formulation of high dose biotin, which serves as a cofactor for essential carboxylase enzymes required for fatty acid synthesis, has recently been demonstrated to provide benefit in patients with not-active progressive multiple sclerosis 39 . Intriguingly, taurine has previously been identified as a dysregulated metabolite in animal models of multiple sclerosis disease, including nonhuman primate models 40 , and its plasma levels can be used to distinguish PLP-induced experimental autoimmune encephalomyelitis (EAE) mice from naive controls 4144 . At a minimum, these findings demonstrate the utility of global metabolomic analyses in the identification of endogenous metabolites that can serve to modulate cellular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…25 Despite the high-rate of misdiagnosis, little attention has been paid toward the analysis of urinary metabolites for diagnosing MS. 26 To address this oversight, we previously demonstrated that urinary metabolites can differentiate between EAE mice (prototypic disease model for MS) from healthy and fingolimod (MS drug)-treated EAE mice. 17 We extended this initial animal study by using NMR, multivariate statistics, one-way ANOVA, and univariate statistics to analyze changes in urine samples collected from MS and NMO-SD patients. Although the sample size was limited, we were still able to observe a potentially unique metabolic signature in urine samples collected from MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 We previously reported an NMR metabolomics analysis of urinary markers of MS using the animal model experimental autoimmune encephalomyelitis (EAE). 17 The results of our prior EAE animal study demonstrated the potential of using urine as a source of metabolite biomarkers for MS. Herein, we report an NMR metabolomics analysis of human urine samples collected from healthy controls, MS patients, and NMO-SD patients. Our results demonstrate a statistically significant difference in the urinary metabolites observed between MS patients and healthy controls and between MS and NMO-SD patients.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, metabolic profiling can provide a window to the instantaneous physiological or pathological changes as a complement to transcriptomic and proteomic profiling for the systematic and functional study of living organisms (6,7). Recent reports are implicating the importance of metabolomics in the possible identification of biomarkers in neurological disorders, including Alzheimer disease (8,9), Parkinson disease (10), and in animal models of MS (11)(12)(13)(14). We have previously performed a comprehensive analysis of plasma metabolites in the RR preclinical mouse model of MS (SJL-experimental autoimmune encephalitis (EAE)) (14) and identified 44 metabolites that distinguished the EAE from control mice.…”
mentioning
confidence: 99%